基于设计计算的齿轮三维设计系统的研究 - 赵韩; 吴振华; 陈兴玉; 宋小波 (Jixie chuandong)
A design system for strength designing and geometrical modeling of gear is realized in SolidWorks;the fundamental methods and process of the secondary development of SolidWorks under the VC environment is presented;Taking the standard involute helical gear as example,the key technologies of building the three dimensional model with SolidWorks API is discussed in detail.